This is how we do it: Methodology of pottery processing at Sagalassos - Poblome, Jeroen; Bes, Philip (Rei Cretariae Romanae Fautorum Acta, 2022)
In this paper, we wish to present the main elements of the way we classify, process, date and store ceramic data related to the archaeological site of Sagalassos (SW Turkey), in particular that from Roman Imperial to Early Byzantine loci from excavations in the ancient urban zone. Following an explanation of the main building blocks according to which pottery finds are being classified – fabric, functional category, and type/variant – a few examples and illustrations serve to illustrate the way in which we work. The so-called ‘Sagalassos Pottery Template’ that was created to this end allows to process all ceramic finds from an individual locus. The paper concludes with highlighting some current and future undertakings regarding the study of pottery and of finds more generally, and ways to integrate these into a single platform.